Effectiveness of Utilization of Facilities and Infrastructure in the Education and Culture Office of Soppeng Regency - Muh. Darwis; Nur Alfiah; Jamaluddin Jamaluddin (Journal of Public Policy and Local Government (JPPLG), 2024)
Utilization of facilities and infrastructure is one indicator to measure the level of good or bad services provided by an institution. This study aims to determine the effectiveness of the use of facilities and infrastructure in the Education and Culture Office of Soppeng Regency. Research is qualitative, therefore, to achieve a research objective, data collection techniques are used, namely observation, interviews, and observation. The informants of this research were 5 employees of the Soppeng Regency Education and Culture Office. Based on the results of the study, it shows that the effectiveness of the use of facilities and infrastructure in the Soppeng Soppeng Regency Education and Culture Office can be seen from the indicators of efficiency, flexibility, satisfaction, and development have been "effective". It can be seen from the dimension of efficiency, namely the availability of adequate facilities and infrastructure as well as the use of facilities and infrastructure that reduce waste of time, energy, efficiency and achieve optimal efficiency has been carried out properly so that employees can carry out their duties and responsibilities to achieve goals. From the dimension of flexibility of facilities and infrastructure, it can be seen from the availability and use of facilities and infrastructure that are flexible enough to make it easier for employees to do various types of work to provide benefits for employees in increasing work effectiveness and supporting office work. From the satisfaction dimension, namely the feeling of pleasure felt by employees after using good facilities and infrastructure to obtain satisfactory work results to increase employee performance and morale in office activities. From the development dimension, the implementation of the development of office facilities and infrastructure used by employees’ functions well and is used properly. The development of office facilities and infrastructure is carried out by the procurement of facilities and infrastructure in collaboration with planning and finance for the development of more adequate facilities and infrastructure.